Orchid’s diversity at Tepequém’s Tepuy, Roraima, Brazil - Nobrega, Sanna Rocha; Luz, Francisco Joaci de Freitas; Oliveira, Jane Maria Franco de; Araújo, Wellington Farias; Tomé, Silvio Garcia (Ornamental Horticulture, 2016)
The Orchidaceae family is one of the largest among the angiosperm, with more than 27000 species, 2,500 is endemic to Brazil, 871 species are found in the Brazilian Amazon. In the far north of Brazil, in the state of Roraima, is located the Tepequém Mountains, a Tepuy – mountain top with table shape – with relictual vegetation due to prolonged isolation. Historically, Tepequém was a site of diamond exploration, which caused changes in the landscape. However, with mining decay, ecotourism became the main economic activity. About 68% of Roraima’s territory is composed of conservation areas and indigenous lands, and the Tepequém Mountain is the only Tepuy found outside the protected areas. Thus, this study aims to describe the orchid flora found at Tepequém’s Tepuy, an area of ecological and economic importance for Roraima’s ecotourism. The survey was carried out through expeditions between the years of 2013-2015. The species were photographed, harvested and taken to Embrapa Roraima for identification, exsiccate confection and/or cultivation. The exsiccatae were deposited at Roraima’s Integrated Museum (Museu Integrado de Roraima – MIRR) and the Federal University of Roraima (Universidade Federal de Roraima – UFRR). Any orchid species deposited by other collectors was also considered. Thus, 20 genera and 34 species were registered at Tepequém. The genera with largest representation were the Epidendrum (7 spp.), Scaphyglottis (4 spp.) and Habenaria (3 spp.), with 70% of the other genera presenting one species only. 10% of Roraima’s orchid’s diversity is found at Tepequém. The diversity of habitats – forest, campina and savannah – found at Tepequém’s Tepuy allows the Orchidaceae species diversity and the unique flora with low similarities to other floristic surveys.